Mathematical proof: meaning, types, attributed functions, and relevance as part of math teachers’ professional knowledge - Alfaro-Carvajal, Cristian (2019)
The objective of this paper is to conduct a theoretical study on the meaning of mathematical proof, taking into consideration three main elements: concept, types, and functions. This is a qualitative and descriptive research. The method used to collect and analyze information is the conceptual analysis. Four sources of information were considered: dictionaries, textbooks, previous research, and the mathematics curriculum of the Ministry of Public Education of Costa Rica. The technique for collecting the information was the bibliographic review. It was determined that proof has different meanings depending on the context; that the types of mathematical proof can be classified into two categories, direct and indirect; and that there are different functions attributed to mathematical proof which are relevant depending on the field in which they are considered. Consequently, the three previous elements should be part of math teachers’ specialized knowledge to promote math proof in secondary education.